A Si Photocathode Protected and Activated with a Ti and Ni Composite Film for Solar Hydrogen Production. Issue 10 (4th February 2015) - Lai, Yi‐Hsuan; Park, Hyun S.; Zhang, Jenny Z.; Matthews, Peter D.; Wright, Dominic S.; Reisner, Erwin
Abstract: An efficient, stable and scalable hybrid photoelectrode for visible‐light‐driven H2 generation in an aqueous pH 9.2 electrolyte solution is reported. The photocathode consists of a p ‐type Si substrate layered with a Ti and Ni‐containing composite film, which acts as both a protection and electrocatalyst layer on the Si substrate. The film is prepared by the simple drop casting of the molecular single‐source precursor, [Ti2 (OEt)9 (NiCl)2 ] (TiNipre ), onto the p‐Si surface at room temperature, followed by cathodic in situ activation to form the catalytically active TiNi film (TiNicat ). The p‐Si|TiNicat photocathode exhibits prolonged hydrogen generation with a stable photocurrent of approximately −5 mA cm −2 at 0 V vs. RHE in an aqueous pH 9.2 borate solution for several hours, and serves as a benchmark non‐noble photocathode for solar H2 evolution that operates efficiently under neutral–alkaline conditions. Abstract : A benchmark non‐noble photocathode : An efficient, stable, and scalable photocathode containing solely earth‐abundant materials effects solar H2 evolution under near neutral pH. Figure (a) shows a p ‐type silicon electrode modified with a Ti and Ni composite film with high activity under solar light illumination. Figure (b) shows the stable photocurrent generated with this hybrid photocathode.